Efficacy and safety of anti-PD-1/PD-L1 antibodies in patients with relapsed refractory diffuse large B-cell lymphoma: A meta-analysis - Zhang Jiawen; Xu Lei; Sun Caifeng; Huang Zonghua; Ma Ji; Wang Liang (Open Life Sciences)
This article conducts a meta-analysis to evaluate the safety and efficacy of PD-1/PD-L1 inhibitors in patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). A total of 63 papers were initially retrieved, and eight clinical studies were collected. The estimated effect of ORR was [OR = 0.40, 95% CI 0.29–0.51; p = 0.08], the estimated effect of complete response rate was [OR = 0.21, 95% CI 0.14–0.31; p < 0.001], while the estimated effect of 1-year progression-free survival was [OR = 0.33, 95% CI 0.22–0.47; p = 0.01]. The estimated effect of 1-year OS was [OR = 0.67, 95% CI 0.55–0.77; p = 0.05]. In addition, the estimated effect of grade 3 adverse events was [OR = 0.33, 95% CI 0.22–0.46; p = 0.01]. Overall, PD-1/PD-L1 inhibitors demonstrated suboptimal therapeutic efficacy in the selected trials for R/R DLBCL. However, combining PD-1/PD-L1 inhibitors with CAR-T showed potential for improved treatment outcomes. Additionally, PD-1/PD-L1 inhibitors were found to be safe and well-tolerated in patients with R/R DLBCL.